Peran Tasawuf dalam Membentuk Pendidikan Karakter Generasi Muda di Era Modern - Rian Setiawan; Pamuji Dwi Prasetyo; Muhamad Iqbal; Bagas Putra Pratama; M. Agus kurniawan P.; Ismail Mubarok; Dede Nur Zaman (International Forum of Researchers and Lecturers, 2026)
The development of digital technology brings significant moral challenges to the younger generation, such as cyberbullying and declining ethics in social interactions. This research aims to examine the role of Sufism in shaping character education in the modern era. The method used is a literature study by analyzing various relevant scientific sources. The results of the study show that the values of Sufism, such as sincerity, patience, tawadhu', and muhasabah, contribute to building self-control, integrity, and social concern. These values can be internalized through value-based education and spiritual activities in schools, so as to strengthen the character of the young generation with noble character. Sufism serves not only as a spiritual teaching, but also as a relevant moral foundation in dealing with the complexities of modern life. Thus, Sufism has a strategic role in forming a generation that has integrity, empathy, and is ready to face the challenges of the times. This research provides a theoretical contribution to the development of character education studies based on Islamic spirituality as well as practical contributions for educational institutions in designing moral development programs that are adaptive to the development of digital technology.